Optimization of the operation of a municipal wastewater treatment plant with hydrocotyle ranunculoides - Quispe, Rebeca (2019)
The objective of the study was to optimize the operation of the municipal wastewater treatment plant (WWTP) of Sicaya district with Hydrocotyle ranunculoides. The relative growth rate of the macrophyte was determined and so the relationship between the population growth area and the final weight according to the number of days elapsed. Medium fences were implemented and the tributary and effluent of the WWTP were characterized physicochemically and microbiologically. The results of the characterization corresponding to the tributary were: 616 mg of TSS/L, 109.2 mg of BOD5/L, 305.4 mg of COD/L, 30.3 mg of oils and fats/L and 3 500 000 NMP of thermotolerant coliforms/100 ml. Owing to the implementation of two medium grids large suspended solids were retained. The highest efficiency of COD removal with respect to the growth area of H. ranunculoides (2 226.96 m2) was 81.53%. While the efficiency of removal of thermotolerant coliforms was 79.2% at a temperature of 12.32 °C of the water. Using the operational optimization model in the WWTP with H. ranunculoides, an area of 3 291.67 m2 of macrophyte population growth was achieved with a removal efficiency of 93.71% COD and an area of 3 591.67m2 to remove 79.95% of thermotolerant coliforms at a temperature of 13°C.